Inhibitory activities of Cystoseira crinita sulfated polysaccharide on key enzymes related to diabetes and hypertension: in vitro and animal study. (1st January 2017) - Ben Gara, Amel; Ben Abdallah Kolsi, Rihab; Jardak, Neila; Chaaben, Rim; El-Feki, Abdelfattah; Fki, Lotfi; Belghith, Hafedh; Belghith, Karima
Abstract: The present study investigated the effect of the Cystoseira crinita sulfated polysaccharide (CCSP) on key enzymes activities related to diabetes in vitro and in diabetic rats. We found that CCSP inhibited pancreatic α-amylase with IC50 = 39.16 μg/ml and angiotensin I-converting enzyme (ACE) activity with IC50 = 58.35 μg/ml in vitro . In diabetic rats, the administration of CCSP reduced the activity of α-amylase in serum, pancreas, and intestine by 23%, 44.38%, and 45%, respectively as compared to untreated diabetic rats. Moreover, the administration of CCSP to surviving diabetic rats protects pancreas β cells from death and damage, which leads to insulin levels. The decrease in α-amylase and the increase in insulin level lead to a decrease in glucose rate by 56% as compared to untreated diabetic rats. The inhibitory action of α-amylase activity and hypoglycemic effect of CCSP were confirmed by oral glucose tolerance test (OGTT). In addition, the administration of CCSP to surviving diabetic rats normalizes lipid profile, stimulates antioxidant capacity, and prevents liver–kidney toxicities, evidenced by decrease in serum indices of liver and kidney toxicity and confirmed by histological analysis. The overall findings presented in this study demonstrate that the administration of CCSP to diabetic rats can make it a potentially strong candidate for industrial application as a pharmacological agent for the treatment of hyperglycemia, hyperlipidemia, and liver–kidney dysfunctions.